1991
DOI: 10.1051/agro:19910306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photon flux density and fluctuation on the nitrogen fixing Glycine max (L Merr)-Bradyrhizobium japonicum symbiosis in a controlled environment

Abstract: Summary — Nodulated soybeans, Glycine max (L Merr), were grown under 6 photon flux densities (PFD) from 0.35-1.03 mmol photons m -2 ·s -1 , in order to determine the optimal light intensity for symbiotic nitrogen fixation in controlled environment. The nitrogenase activity (C 2 H 2 reduction) was highest at 0.68 mmol photons m -2 ·s -1 which also corresponded to the highest growth of plants and the biggest mass of nodules. The specific acetylene reducing activity was not affected by PFD, (fig 1). L'ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…3B). This observation is more similar to those reported in studies of long-term, continuous exposure of soybean (Drevon et al, 1991) and peas (Sheikholeslam et al, 1980) to different light intensities. These studies indicated that longterm differences in photosynthate supply affected nodule mass and not specific nitrogenase activity.…”
Section: Controlled-environment Studysupporting
confidence: 90%
“…3B). This observation is more similar to those reported in studies of long-term, continuous exposure of soybean (Drevon et al, 1991) and peas (Sheikholeslam et al, 1980) to different light intensities. These studies indicated that longterm differences in photosynthate supply affected nodule mass and not specific nitrogenase activity.…”
Section: Controlled-environment Studysupporting
confidence: 90%
“…The relative tolerance of some lines seems to depend on their ability to maintain an adequate leaf area insuring an important carbon supply permitting the development of an abundant and efficient nodular system, which in turn determines an important rate of nitrogen fixation and permits the plants to conserve their growth potentialities. The same behaviour has been observed in Glycine max-Bradyrhizobium japonicum symbiosis [8]. More work is needed to search at the nodules level, the physiological mechanisms involved in the lines differences in their sensitivity, and to explore a larger number of lines for more tolerant parents.…”
Section: Discussionsupporting
confidence: 62%